Regarding humanity: interwoven intricacies of universality and unity - Clark, Sandra S., author; Lundberg, Thomas R., advisor; Moseman, Eleanor, committee member; Faris, Suzanne, committee member; Volbrecht, Vicki, committee member (Colorado State University. Libraries, 2013)
In order to communicate, organize and understand the world around them, people from the earliest times have established semiotic language systems, mathematics, social structures and religions. Through layered symbolism, the mathematically driven work discussed here ruminates on these common developments. Each component is individually crafted, bringing value to each unit of the overall pattern. While there are slight variations, as in humanity, these components are all basically the same. This installation is intended to draw attention to the beauty of the whole. Regarding Humanity offers my interpretation of these cultural developments and what I view as the fundamental, intellectual needs of people all over the world.
Keywords: fiber; installation; sculpture; steel; tessellation; weaving